2012
DOI: 10.1002/hep.25698
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte senescence in vivo following preconditioning for liver repopulation

Abstract: In the retrorsine (RS)-based model of massive liver repopulation, preexposure to this naturally occurring alkaloid is sufficient to prime normal host parenchymal cells to be slowly replaced by transplanted normal hepatocytes. The basis for this striking effect is yet to be fully elucidated. In the present studies the possible involvement of cell senescence was investigated. Fischer 344 rats were treated according to the RS-based protocol for hepatocyte transplantation, i.e., two doses of RS, 2 weeks apart, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…Furthermore, a main component of SASP/SMS, namely the pro-inflammatory cytokine IL-6, was also over-expressed in DENA+RS-treated animals. Both findings were in agreement with those reported following exposure to RS alone [10]. …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, a main component of SASP/SMS, namely the pro-inflammatory cytokine IL-6, was also over-expressed in DENA+RS-treated animals. Both findings were in agreement with those reported following exposure to RS alone [10]. …”
Section: Resultssupporting
confidence: 93%
“…As mentioned in the Introduction, recent findings have indicated that exposure to RS induces extensive hepatocyte senescence in rat liver [10]. Although cell senescence can represent a fail safe mechanism to alt neoplastic progression of altered cells [17], it is now well established that it can also contribute to the emergence of the neoplastic phenotype, possibly through secretion of a host of factors, variably referred to as senescence-associated secretory phenotype (SASP) [18] or senescence-messaging secretome (SMS) [19], and comprising cytokines, growth factors and proteases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite clinical improvements in patients, significant problems have arisen because of inefficient engraftment, death or ectopic distribution of cells that did not engraft in the target tissue, emboli formation, immunological rejection, and transient effects of transplanted cells [34][35][36]. A number of preconditioning regimens including irradiation or chemicals have been tried but discontinued for various reasons such as senescence, radiation hazards, or an increased risk of cancer [37,38].…”
Section: Discussionmentioning
confidence: 99%